Two-dimensional extended warranty length design from incomplete warranty data based on a new price curve considering different maintenance policies. (August 2022) - Gupta, Sanjib Kumar; Mukhopadhyay, Indranil; Chatterjee, Aditya
Abstract: The extended warranty issue is concerned with additional after-sale protection for a consumer, at the cost of an extra premium. Depending upon the reliability and durability of the components or the system, the extension of warranty may be done with regard to either age or usage or both, for those specified components or the entire system. The age-based analysis is usually referred to as the one-dimensional problem, while age along with usage-based analysis is termed as the two-dimensional problem. By considering two factors, v i z . premium ceiling and premium escalation rate, respectively indicating the maximum allowable premium and the rate at which the allowable premium is raised with the increased coverage, the present paper deals with the design of a new price curve based optimum extended warranty policies corresponding to perfect, minimal, and imperfect repairs, for both one- and two-dimensional problems. The availability and use of incomplete field data on age and usage, facilitate establishing the relative advantage of the two-dimensional modeling over its one-dimensional counterpart, while considering an extension of the baseline warranty coverage. The findings have been elaborated with the help of a synthetic real-life data. Highlights: Two-dimensional baseline warranty coverage in terms of age and usage is extended. Warranty cost analysis is conducted based on premium ceiling and escalation rate. The optimum extended warranty coverage safeguards the interest of manufacturer and buyer. The change of warranty coverage with premium ceiling and escalation rate is studied.